Motor speed controller using fuzzy logic method for PCB drilling operation - Khairul Azmil, Adzmi (2008)
This thesis is generally about how the mechanical system reacts when a load is given or friction is happen to touch the mechanical system. Every mechanical system will always be affected when there is a disturbance. Drilling operation is one of the common operations in the industry. When the drilling operation works, there must be a friction occurs when the work is done. Thus, there will be lack of performance for the drilling machine. The lack of the performance of the drilling machine will lead to the speed of the machine that will decrease slightly. That is the main part of this project. To make the performance of the drilling machine maintain, the speed must be increase as soon the friction is given to the drilling machine. To solve the problem, the Fuzzy Logic Method is use in this project. Using Fuzzy Logic Method, new equation will be finding and use it for this project. From the method, the speed of the motor will increase when the drilling operation is given a friction. There will be feedback for the error that the sensors detect from the drilling machine. The feedback will calculate the error and from the calculation the new increasing voltage will be determined. For the conclusion, the method is trying to find the new voltage for the drilling machine to maintain the speed of the machine. From the fact, we know that when the voltage in increase, the speed will also increase. Thus, the performance of the drilling machine will become more efficient.